A study of Female Sex worker’s sub-network on STI treatment seeking behavior in Chennai City: A Social Network Approach - Annadurai, Kabilan; Bagavandas, M (Indian Journal of Community Health, 2017)
Background: Female Sex workers (FSW) are having high-risk sexual behavior with multiple partners and the periodical sexually transmitted infection screening is determined by various factors. Aims & Objectives: To explore the presence of sub-networks of FSWs and to identify the trends in information flow on Sexually Transmitted Infection (STI) treatment seeking behavior by using social network analysis (SNA). Material & Methods: This was a community-based cross-sectional study and exponential snowball sampling method is used to identify 420 FSWs. Structured questionnaire was used to measure information flow and sub-network characteristics of social relationship, Information & Treatment seeking for STI and Sexual practice. Results: Study has listed 94 sub-networks. Here, Sexual practice (Sub-group 28) has highest number of subnetworks compared to other three subnetworks of Social Relationship (Sub-group 25), information on STI (Sub-group 23) and Treatment seeking for STI (Sub-group18). Similarly, other Centrality measures like Triad and Dyad are higher (Each 4 sub-group) in sexual practice domain and this is absent in rest of the three domains. Further, treatment seeking for STI has low Clique (Sub-group 17) compared to other domains. This shows high information flow is present in Sexual Practice compare to treatment seeking for STI (CC-0.986, P-0.000). Among the sub typology home based and street based FSWs are well connected, well informed and most influential than other sub-typology. Conclusion: SNA reaches more number of HRGs with less resource. Therefore, SNA could be cost effective to mapping the sub-network and visualize the information path for STI treatment seeking behavior